Bait and Switch: How Do Chinese Firms Use Proceeds from Seasoned Equity Offerings - Hong Bo; Zhongnan Huang; Elmer Sterken (Center for Economic Studies and ifo Institute (CESifo), 2015)
We reveal motivations of Chinese firms for issuing Seasoned Equity Offerings (SEO) by examining why firms change the use of SEO proceeds and how they use unspecified SEO proceeds. Using 533 SEOs issued by Chinese firms during 1999-2006, we find that firms do not use unspecified SEO proceeds on capital investment regardless of the nature of controlling shareholders. We find that if the controlling shareholder is the state, then the firm uses unspecified proceeds to stockpile cash; if the controlling shareholder is a parent state-owned enterprise, then the firm uses unspecified proceeds on retiring debt and on related party transactions.
Keywords: G30; G32; L20; 330; Seasoned Equity Offerings (SEO); use of SEO proceeds; SEO motives; controlling shareholders